Impact of Service Quality on Satisfaction, Loyalty and Intention to Revisit of Sport Customers: The Case Study of Swimming Pools in Alborz Province - Barshan, Gholamreza; Elahi, Alireza; Aghaei, Najaf (International Review of Management and Marketing, 2017)
The aim of this research was to determine the effect of customer satisfaction and loyalty attitude and willingness of the pools was Alborz Province. The research methodology was correlational the field. The population of this study was all Alborz province pools, male customers were used for the completion of questionnaires. The samples of this study were 361 persons. The questionnaire used in the study consisted of Loyalty questionnaire of Allan (2004), service quality and satisfaction scale of Liu, (2008) and intention to revisit of Lim (2006). The face and content validity is confirmed by panel of experts and thr reliability of components was estimated by Cronbach's Alpha in this way: satisfaction (0.913), attitudinal (0.754), and attendance tendency (0.696). Data analysis was performed using LISREL software. In Diagram 1 LISREL software output is in standard mode. Results LISREL output indicates that the dimension of quality of services including tangibility, reliability, responsiveness, assurance and empathy have the effect of.33, .16, .15, .21 and .27 percent on overall satisfaction respectively. Also attitudinal loyalty has the effect on .61 percent and behavioral loyalty has the effect of .24 on intention to revisit of customers. Keywords: Satisfaction, attitudinal loyalty, sport, intention to revisit JEL Classifications: M31, M37, Z32